Role of Phosphatidylinositol 3-Kinase (PI3K), Mitogen-Activated Protein Kinase (MAPK), and Protein Kinase C (PKC) in Calcium Signaling Pathways Linked to the α1-Adrenoceptor in Resistance Arteries - Gutiérrez, Alejandro; Contreras, Cristina; Sánchez, Ana; Prieto, Dolores (Frontiers in Physiology, 2019)
Insulin resistance plays a key role in the pathogenesis of type 2 diabetes and is also related to other health problems like obesity, hypertension, and metabolic syndrome. Imbalance between insulin vascular actions via the phosphatidylinositol 3-Kinase (PI3K) and the mitogen activated protein kinase (MAPK) signaling pathways during insulin resistant states results in impaired endothelial PI3K/eNOS- and augmented MAPK/endothelin 1 pathways leading to endothelial dysfunction and abnormal vasoconstriction. The role of PI3K, MAPK, and protein kinase C (PKC) in Ca2+ handling of resistance arteries involved in blood pressure regulation is poorly understood. Therefore, we assessed here whether PI3K, MAPK, and PKC play a role in the Ca2+ signaling pathways linked to adrenergic vasoconstriction in resistance arteries. Simultaneous measurements of intracellular calcium concentration ([Ca2+]i) in vascular smooth muscle (VSM) and tension were performed in endothelium-denuded branches of mesenteric arteries from Wistar rats mounted in a microvascular myographs. Responses to CaCl2 were assessed in arteries activated with phenylephrine (PE) and kept in Ca2+-free solution, in the absence and presence of the selective antagonist of L-type Ca2+ channels nifedipine, cyclopiazonic acid (CPA) to block sarcoplasmic reticulum (SR) intracellular Ca2+ release or specific inhibitors of PI3K, ERK-MAPK, or PKC. Activation of α1-adrenoceptors with PE stimulated both intracellular Ca2+ mobilization and Ca2+ entry along with contraction in resistance arteries. Both [Ca2+]i and contractile responses were inhibited by nifedipine while CPA abolished intracellular Ca2+ mobilization and modestly reduced Ca2+ entry suggesting that α1-adrenergic vasoconstriction is largely dependent Ca2+ influx through L-type Ca2+ channel and to a lesser extent through store-operated Ca2+ channels. Inhibition of ERK-MAPK did not alter intracellular Ca2+ mobilization but largely reduced L-type Ca2+ entry elicited by PE without altering vasoconstriction. The PI3K blocker LY-294002 moderately reduced intracellular Ca2+ release, Ca2+ entry and contraction induced by the α1-adrenoceptor agonist, while PKC inhibition decreased PE-elicited Ca2+ entry and to a lesser extent contraction without affecting intracellular Ca2+ mobilization. Under conditions of ryanodine receptor (RyR) blockade to inhibit Ca2+-induced Ca2+-release (CICR), inhibitors of PI3K, ERK-MAPK, or PKC significantly reduced [Ca2+]i increases but not contraction elicited by high K+ depolarization suggesting an activation of L-type Ca2+ entry in VSM independent of RyR. In summary, our results demonstrate that PI3K, ERK-MAPK, and PKC regulate Ca2+ handling coupled to the α1-adrenoceptor in VSM of resistance arteries and related to both contractile and non-contractile functions. These kinases represent potential pharmacological targets in pathologies associated to vascular dysfunction and abnormal Ca2+ handling such as obesity, hypertension and diabetes mellitus, in which these signaling pathways are profoundly impaired.